Comparison of effective I‐131 half‐life between thyroid hormone withdrawal and recombinant human thyroid‐stimulating hormone for thyroid cancer: A retrospective study. Issue 2 (6th October 2014) - Grenfell, Solveig; Roos, Daniel; Rijken, James; Higgs, Braden; Kirkwood, Ian
Abstract Introduction Preparation for postoperative radioiodine ablation for differentiated thyroid carcinoma is performed by either thyroid hormone withdrawal or recombinant human thyroid‐stimulating hormone (rhTSH) administration. There is little information on the impact of the method of preparation with respect to whole‐body effective I‐131 half‐life and its potential clinical implications in the Australian setting. Methods A retrospective study was performed on patients admitted for adjuvant radioiodine ablation for non‐metastatic differentiated thyroid carcinoma at the Royal Adelaide Hospital over a 4½‐year period from 2009. Dose rate measurements were analysed for 19 rhTSH and 31 thyroid hormone withdrawal patients. Results The mean effective I‐131 half‐lives were 11.51 and 13.29 h for the rhTSH and thyroid hormone withdrawal groups, respectively, with no statistically significant difference between the two groups (P = 0.761). This result differs from previously published data where withdrawal periods were typically longer, resulting in slower renal clearance and longer half‐lives for withdrawal patients. Conclusions Our study did not demonstrate a significant difference in whole‐body effective half‐life of I‐131 between the two methods of preparation for radioiodine ablation. This suggests that putative advantages of rhTSH over withdrawal in terms of whole‐body radiation dose, duration of hospital admission and quality of life may be sensitive to duration of withdrawal.